Association of Rate-Dependent Conduction Block Between Eccentric Coronary Sinus to Left Atrial Connections With Inducible Atrial Fibrillation and Flutter. (January 2017) - Huang, Dong; Marine, Joseph E.; Li, Jing-bo; Zghaib, Tarek; Ipek, Esra Gucuk; Sinha, Sunil; Spragg, David D.; Ashikaga, Hiroshi; Berger, Ronald D.; Calkins, Hugh; Nazarian, Saman
Abstract : Background—: We sought to describe the prevalence and variability of coronary sinus (CS) and left atrial (LA) myocardium connections, their susceptibility to rate-dependent conduction block, and association with atrial fibrillation (AF) and flutter induction. Methods and Results—: The study cohort included 30 consecutive AF patients (age 63.3±10.5 years, 63% male). Multipolar catheters were positioned in the CS, high right atrium (HRA), and LA parallel to and near the CS. Trains of 10 pacing stimuli were delivered during sinus rhythm from each of the following sites: CS proximal (CSp ), CS distal (CSd ), LA septum (LAs ), lateral LA (LAl ), and HRA, at the following cycle lengths: 1000, 500, 400, 300, and 250 ms, while recording from the other catheters. With the CS 9 to 10 bipole just inside the CS ostium, CS–LA connections were observed in 100% at CS 9 to 10, 30% at CS 7 to 8, 23% at CS 5 to 6, 23% at CS 3 to 4, and 97% at CS 1 to 2. Eighteen patients (60%) had AF/atrial flutter induced. Rate-dependent conduction block of a CS–LA connection at cycle length of ≥250 ms was present in 17 (94%) of those with versus none of those without AF/atrial flutter induction ( P <0.001). Conclusions—: Rate-dependent eccentric CS–LA conduction block is associated with AF/atrial flutter induction in patients with drug-refractory AF undergoing ablation. The presence of dual muscular CS–LA connections, coupled with unidirectional block in one limb, seems to serve as a substrate for single or multiple reentry beats, and arrhythmia induction.